The effects of particle injections on the ring current development during the 7-8 September 2017 geomagnetic storm - Ferradas, C. P.; Fok, M.-C.; Maruyama, N.; Henderson, M. G.; Califf, S.; Thaller, S. A.; Kress, B. T. (Frontiers in Astronomy and Space Sciences, 2023)
In this study we investigate the role of particle injections on the ring current development during the 7-8 September 2017 geomagnetic storm by applying a temporally and spatially varying data-driven outer boundary condition in numerical simulations of the ring current with the Comprehensive Inner Magnetosphere-Ionosphere model. We quantify the role of particle injections by comparing the results from two simulation runs: one with the model outer boundary condition defined by measurements at their original time cadence, namely 1.5 min, and one with the same boundary condition smoothed in time with a 2-h running average window. The comparison between these two runs reveals that the observed particle injections enhanced the electric field remarkably, which had a significant effect on the ring current development, namely, they (1) strengthened the ring current, (2) skewed the ring current distribution dawnward, (3) delayed the formation of the symmetric ring current by prolonging the duration of the partial ring current, and (4) caused a O + -richer ring current with a O + dominant ring current distribution at the inner edge. Furthermore, these effects enhanced the energy deposition to the plasmasphere and ionosphere via heating by the ring current ions.The ring current is one of the four major particle populations in the inner magnetosphere, the other three being the cold plasmasphere, the warm plasma cloak, and the relativistic radiation belts. The ring current is composed of ions and electrons of a few keV to a few hundred keV flowing around the Earth at geocentric distances of ~2-6 Earth radii (RE), and its spatial distribution overlaps with the other inner magnetospheric particle populations, creating a highly dynamic and complex environment. As the particle